(untitled) (African Journal of Science, Technology and Social Sciences, 2024)
Safe management of faecal waste is one of the Sustainable Development Goals (SDGs) which envisions safe sanitation for all. However, although efforts to improve sanitation conditions in slums have been made, faecal emptying, conveyance and disposal still remain a challenge endangering the health of the public. The study examined the influence of economic factors on faecal emptying, conveyance and disposal in on-site sanitation facilities in Meru slums. A convergent design with a mixed methods approach was adopted. Quantitative data was collected using structured questionnaires from a sample of 228 household heads selected using cluster and proportionate simple random sampling techniques. Correlation and regression analysis was carried out to ascertain the association between emptying, conveyance and disposal of faecal waste and the economic factors. Qualitative data was gathered using focus group discussion participants with eight (8) who included four (4) pit operators, 3 household heads and 1 Public Health Officer (PHO) and results analyzed thematically. Findings showed that only 31% of slum dwellers emptied latrine pits and that manual emptying was more common (84%) than mechanical emptying because of its cost efficiency, reliability and the effectiveness in handling plastics, glasses, metal pieces, diapers and sanitary pads contained in pits. Increased cost constrained faecal emptying, conveyance, and disposal (r=0.499, p-value=0.000). Residents who were able to pay for faecal handling services were more likely to practice hygienic faecal emptying, conveyance, and disposal (r=0.524, p-value=0.000). Low level of income for majority of slum dwellers influenced the design of the latrines adopted. Emptying faeces from poorly designed pit latrines was more expensive due to operators’ safety concerns. The study concluded that the inability to meet the costs associated with faecal emptying, conveyance and disposal services facilitated poor sanitation status in slums. There is need to sensitize the slum community on the benefits of practicing safe management of faecal waste. The study recommended development of government policies to regulate mechanical emptying conveyance and disposal of faecal matter.